BHMN PT: MENUJU KAPITALISME PENDIDIKAN - sulardi, sulardi (Jurnal Bestari, 2008)
Education in Indonesia seems not providing better future for students because the recent policy in education tends to lead on capitalization of higher education through PT BHMN. The autonomy issue is perceived to make the cost of education higher. However, UUD 1945 allows the 25% of national funds for education purpose for making the education reachable ofr every one.May party reject the policy of PT BHMN with the arguments that PT BHMN has changed the visions of education: education to enlighten people is no more achieved, only few parts of people can achieve it. It is assumed that capitalism plays role in this sociable and agricultural country.